Standardization vs. multiplicity of medical recipe compositions – a computational reconstruction of the genealogy of TCM recipes - Prackwieser, Joachim (2023)
Standardization of medical recipes plays an important role in present day Traditional Chinese Medicine (TCM) research as part of an effort to promote TCM as a reliable medicine in China and worldwide. To this end, not only necessary quality and safety control standards of recipe ingredients are implemented, but also historically varying compositions of recipes need to be reduced to one standardized sequence of ingredients and dosages. This paper draws on the notion of recipes as an “epistemic genre” to look at recipes not just as a sequence of ingredients but as vehicles of knowledge transmission. Recipes seen as a genre connect the rich past of Chinese medicine with modern day standardized TCM, thus representing continuity and change at once. By focusing specifically on established recipes in Chinese medical history that are still in use today, this paper will analyze how these recipes have changed in their composition over time through computational comparison. By grouping similar recipes through clustering algorithms, influences from lineages of medical thought as well as from different societal strata may become apparent. This computational approach is based on two only recently accessible datasets. The Polyglot Asian Medicine China corpus contains 392 digital editions of early medical printed texts from 200 CE to the Republican Era in the 20th century. While this dataset covers knowledge transmission within the official discourse, the second dataset represents the recipes collected and used in the local context. This Chinese Historical Healthcare Manuscripts corpus comprises 41,000 digitized and annotated medical recipes from 227 handwritten volumes of local/ rural physicians, itinerant doctors, family households, and medical students for their own use. By looking at what has been “lost” through standardization, an integral part of the recipes as epistemic genre can be recovered - its multiplicity. The tracing of changes in recipe composition over time and their clustering based on a large amount of data allows to review the selection processes leading to the standard recipe in modern TCM and may be a starting point to rethink strict standardization.